Research progress on bearing fault diagnosis with localized defects and distributed defects for rolling element bearings. (July 2022) - Patel, Samruddhi; Shah, Utpal; Khatri, Bharat; Patel, Utkarsh
In rotating machinery, rolling elements are the key members of the rolling element bearing (REB), which has tremendous application in automobiles, aerospace, ships, machinery apparatuses, and many more industrial sectors. Bearings are a significant source of various non-linear parameters which strongly affect the whole system. In the last two decades, tremendous research and approaches have been developed, considering the different parameters and faultiness for the proper understanding of the system's non-linear behavior. This research paper summarizes the literature review on bearing fault diagnosis with localized and distributed defects for rolling element bearings with various non-linear parameters. Artificially-generated defects on the bearing races provides the vibration analysis of the system. These factors like radial clearance, unbalanced force, preload, misalignment, etc. are also considered defects in bearings. Moreover, the literature highlights some significant gaps that should be examined for future research in the condition monitoring of the mechanism.